Estudo paramétrico da inserção de estrutura do tipo dgs com geometria baseada em metamaterial do tipo setr (split equilateral triangle resonator) aplicada em antenas de microfita - Araújo, João Kleber Lima de (2020)
Wireless communication systems (Wireless) have been constantly developing due to the demand for higher data transmission speeds, services at different frequencies and applications. Thus, implementations are necessary based on parametric studies, new methods and devices capable of meeting the increased versatility, reliability and scalability of this technology. In this perspective, this work presents a parametric study of return loss, resonant frequency and bandwidth, radiation diagram, current flow density, Smith chart and VSWR (Voltage Standing Wave Ratio) in microstrip antennas with changes in the ground plane, forming DGS (Defected Ground Structures), from the insertion of SETR (Split Equilateral Triangle Resonator) metamaterial elements and simulated in the software HFSS® for theoretical measurements, manufactured and simulated in VNA (Vector Network Analyzer) for practical measurements. With this, comparisons were made between the simulated and measured results, for analysis and verification of the methods and materials, used and manufactured. The results showed that the antennas obtained several resonant modes, in the bands commonly used in telecommunications, between 2.2 GHz and 2.35 GHz and 3.5 GHz and 4.1 GHz